Association of physical activity, vitamin E levels, and total antioxidant capacity with academic performance and executive functions of adolescents - Ahmad H. Alghadir; Sami A. Gabr; Zaheen A. Iqbal; Einas Al-Eisa (BMC, 2019)
Abstract Background Although various studies have shown the effect of vigorous physical activity on academic achievements, no studies have investigated the effect of vitamin E levels on academic performance. The present study aimed to assess the association between physical activity, vitamin E levels and total antioxidant capacity on the academic performance and executive functions of adolescents aged 15-18 years. Methods The physical activity of participants was assessed according to the time spent engaging in moderate and intense exercise programs. Participants were classified into three groups representing mild, moderate, and high activity. Serum total antioxidant capacity was measured using a colorimetric assay kit. Vitamin E was estimated by the α- and γ-tocopherol levels in fasting serum samples using high-performance liquid chromatography paired with a diode array detector. School grades (ranging from 1.0, very poor; to 10.0, outstanding) were obtained at the end of the academic year to evaluate academic performance and executive functions. Results A total of 120 school students (mean age 16.36 ± 0.77 years; 70 boys, 50 girls) participated in the study. Academic performance was higher for students classified as moderately or highly active compared with those in the mild activity group. Serum levels of vitamin E, total antioxidant capacity, and leisure-time physical activity were also higher in the moderate and high activity groups. There was a significant correlation between age, gender, body mind index, α- and γ-tocopherol, total antioxidant capacity, leisure-time physical activity and academic performance. Conclusions The academic performance and executive function scores were found to be positively correlated with age, gender, α- and γ-tocopherol, total antioxidant capacity, and physical activity; and were negatively correlated with body mind index. Our findings indicate that physical activity should be promoted during and after school hours, along with a healthy balanced diet including vitamin E.